Risk of post-fracture pneumonia and its association with cardiovascular events and mortality in adults with intellectual disabilities - Whitney, Daniel G.; Erickson, Steven R.; Berri, Maryam (Frontiers in Psychiatry, 2023)
Fragility fractures are associated with an increased risk of pneumonia, which is a leading cause of death for adults with intellectual disabilities; yet, the timing and complications of post-fracture pneumonia are understudied. The objectives were to determine the 30-day pneumonia rate post-fracture and its association with mortality and cardiovascular events among adults with intellectual disabilities. This retrospective cohort study used Medicare and commercial claims from 01/01/2011-12/31/2016. Incidence of pneumonia 30-days after a fragility fracture for adults ≥18 years old with intellectual disabilities (Fx cohort) was compared to matched adults with intellectual disabilities without fractures (w/oFx cohort) and the general population with an incident fragility fracture (GP+Fx). For the Fx cohort, Cox regression examined the adjusted association between time-varying pneumonia (within 30-days post-fracture) with mortality and incidence of cardiovascular events 0-30 days, 31-365 days, and 366-730 days post-fracture. There was a high-early rate of 30-day pneumonia post-fracture for young, middle-aged, and elderly adults with intellectual disabilities (n=6,183), which was 2.2- to 6.1-fold higher than w/oFx (n=12,366) and GP+Fx (n=363,995) (all P<0.05). For the Fx cohort, post-fracture 30-day pneumonia was associated with an increased 30-day rate of mortality (adjusted HR [aHR]=5.19; 95%CI=3.68-7.32), heart failure (aHR=2.96; 95%CI=1.92-4.56), and cerebrovascular disease (aHF=1.48; 95% CI=0.93-2.35; P=0.098), with sustained effects to 1-year for heart failure (aHR=1.61; 95%CI=1.19-2.17) and 2-years for mortality (aHR=1.39; 95%CI=1.06-1.83) without evidence of effect modification by age. Adults with intellectual disabilities are vulnerable to 30-day risk of post-fracture pneumonia and its complications across the adult lifespan and not just in the elderly years.